2020
DOI: 10.9734/ajeba/2020/v15i430218
|View full text |Cite
|
Sign up to set email alerts
|

Total Factor Productivity and Environmental Efficiency of the Most Important Cereals Crops in Egypt

Abstract: Purpose of the Study: Egyptian agriculture suffers from many problems related to the use of available economic resources, the most important of which is lack of optimal utilization of resources, wasteful use of agricultural production inputs, reduced efficiency of irrigation water use, and the fertility of agricultural lands are deteriorating, in addition to increasing rates of encroachments on agricultural lands and shifting it from agricultural use to other non-agricultural uses, which limits the agricultura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…In study to examine the expansion of Egypt's three major cereal crops; rice, wheat, and maize, as well as the factors that contributed to these crops' output increases between 1975 and 2017 by, El-Rasoul et al (2020) this study divided to three intervals: 1975-1986, 1987-2000, and 2001-2017, with respect to the whole period 1975-2017, founded on the data concluded of the Chow Breakpoint test. The findings demonstrated that increases in yield, rather than changes in area, were more important for the expansion of wheat, rice, and maize output over the research periods.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…In study to examine the expansion of Egypt's three major cereal crops; rice, wheat, and maize, as well as the factors that contributed to these crops' output increases between 1975 and 2017 by, El-Rasoul et al (2020) this study divided to three intervals: 1975-1986, 1987-2000, and 2001-2017, with respect to the whole period 1975-2017, founded on the data concluded of the Chow Breakpoint test. The findings demonstrated that increases in yield, rather than changes in area, were more important for the expansion of wheat, rice, and maize output over the research periods.…”
Section: Literature Reviewmentioning
confidence: 99%
“…(Gamal et al, 2021). Net exports, corporate investment, government expenditure, personal consumption and population make up the five components of the per capita gross domestic product (El-Rasoul et al, 2020) however these five components can affected by environmental factors in the time of occurrence, like water availability, winter and summer temperatures, and the area's natural resources-such as rivers and coastlines-among others. Each of these elements affects a nation's ability to grow economically.…”
Section: Introductionmentioning
confidence: 99%
“…It is important to assess this type of relationship given that under Covid conditions it was evidenced that the decreasing changes in TFP were mainly due to changes in technical efficiency (EFFCH), this has to do with the people affected by Covid having an impact on the availability of labor in companies. Some authors highlight this importance in the Covid period [49][50][51][52][53][54].…”
Section: Plos Onementioning
confidence: 99%
“…Maize is an annual plant, which forms the backbone of the world's food security since it is consumed by humans and cattle, as well as a source of industrial raw materials for the manufacturing of bioproducts like oil, alcohol, and starch. In 2020, the total cultivated area of maize in Egypt reached 871076.12 hectares (1 hectare = 10.000 m 2 ) with average productivity of 8154,48 tons/ha (El-Rasoul et al, 2020).…”
Section: Introductionmentioning
confidence: 99%